TP53-inducible putative long noncoding RNAs encode functional polypeptides that suppress cell proliferation - Xu, Wenli; Liu, Chang; Deng, Bing; Lin, Penghui; Sun, Zhenghua; Liu, Anrui; Xuan, Jiajia; Li, Yuying; Zhou, Keren; Zhang, Xiaoqin; Huang, Qiaojuan; Zhou, Hui; et al. (Genome Research, 2022)
Polypeptides encoded by long noncoding RNAs (lncRNAs) are a novel class of functional molecules. However, whether these hidden polypeptides participate in the TP53 pathway and play a significant biological role is still unclear. Here, we discover that TP53-regulated lncRNAs can encode peptides, two of which are functional in various human cell lines. Using ribosome profiling and RNA-seq approaches in HepG2 cells, we systematically identified more than 300 novel TP53-regulated lncRNAs and further confirmed that 15 of these TP53-regulated lncRNAs encode peptides. Furthermore, several peptides were validated by mass spectrometry. Ten of the novel translational lncRNAs are directly inducible by TP53 in response to DNA damage. We show that the TP53-inducible peptides TP53LC02 and TP53LC04, but not their lncRNAs, can suppress cell proliferation. TP53LC04 peptide also has a function associated with cell proliferation by regulating the cell cycle in response to DNA damage. This study shows that TP53-regulated lncRNAs can encode new functional peptides, leading to the expansion of the TP53 tumor-suppressor network and providing novel potential targets for cancer therapy.
10.1101/gr.275831.121